Analisis Kelayakan Usaha Tempat Pemotongan Unggas (TPU) di Kecamatan Pulau Laut Sigam Kabupaten Kotabaru - Putra, Muhammad Heriyadi; Biyatmoko, Danang; Riyadhi, Muhammad; Apedro, Henggi; Mufidah, Nisa (www.ulm.ac.id, 2025)
The poultry processing industry, particularly broiler chicken, plays a vital role in meeting the demand for animal protein in Indonesia. The increase in chicken consumption, as recorded by the Ministry of Agriculture (BPS, 2024), creates opportunities for the development of poultry slaughterhouses (TPUs). This study aims to assess the economic feasibility of TPU Pak Nasir in Kotabaru Regency, South Kalimantan. The method used is financial analysis, with calculations of Benefit/Cost Ratio (B/C Ratio) and Break-Even Point (BEP). The results show that TPU Pak Nasir has a B/C Ratio of 1.99, indicating high financial feasibility. The BEP Price of 25,376 IDR/kg and BEP Production of 29,907 chickens per month indicate the minimum price and volume needed to break even. Sensitivity analysis shows that the business can sustain even with a 10% decline in gross revenue and has the potential for higher profits if revenue increases.